Protein 61K, encoded by a gene (PRPF31) linked to autosomal dominant retinitis pigmentosa, is required for U4/U6·U5 tri-snRNP formation and pre-mRNA splicing - Makarova, Olga V. (Oxford University Press, 2002)
In each round of nuclear pre-mRNA splicing, the U4/U6·U5 tri-snRNP must be assembled from U4/U6 and U5 snRNPs, a reaction that is at present poorly understood. We have characterized a 61 kDa protein (61K) found in human U4/U6·U5 tri-snRNPs, which is homologous to yeast Prp31p, and show that it is required for this step. Immunodepletion of protein 61K from HeLa nuclear extracts inhibits tri-snRNP formation and subsequent spliceosome assembly and pre-mRNA splicing. Significantly, complementation with recombinant 61K protein restores each of these steps. Protein 61K is operationally defined as U4/U6 snRNP-specific as it remains bound to this particle at salt concentrations where the tri-snRNP dissociates. However, as shown by two-hybrid analysis and biochemical assays, protein 61K also interacts specifically with the U5 snRNP-associated 102K protein, indicating that it physically tethers U4/U6 to the U5 snRNP to yield the tri-snRNP. Interestingly, protein 61K is encoded by a gene (PRPF31) that has been shown to be linked to autosomal dominant retinitis pigmentosa. Thus, our studies suggest that disruptions in tri-snRNP formation and function resulting from mutations in the 61K protein may contribute to the manifestation of this disease.